2010
DOI: 10.2147/tcrm.s10235
|View full text |Cite
|
Sign up to set email alerts
|

Reduced exercise capacity in persons with Down syndrome: cause, effect, and management

Abstract: Persons with Down syndrome (DS) have reduced peak and submaximal exercise capacity. Because ambulation is one predictor of survival among adults with DS, a review of the current knowledge of the causes, effects, and management of reduced exercise capacity in these individuals would be important. Available data suggest that reduced exercise capacity in persons with DS results from an interaction between low peak oxygen uptake (VO2peak) and poor exercise economy. Of several possible explanations, chronotropic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 95 publications
4
81
0
6
Order By: Relevance
“…The same therapist and technique before the study and after 2 months of the study measured all the parameters of evaluation. It was reported that, subjects with DS have reduced peak and sub-maximal exercise capacity [23]. Our results proved that VC, MVV, SaO 2 and RR significantly improved at the end of the study because of the pulmonary rehabilitation program and these results are in agreement with some previous studies as well.…”
Section: Discussionsupporting
confidence: 93%
“…The same therapist and technique before the study and after 2 months of the study measured all the parameters of evaluation. It was reported that, subjects with DS have reduced peak and sub-maximal exercise capacity [23]. Our results proved that VC, MVV, SaO 2 and RR significantly improved at the end of the study because of the pulmonary rehabilitation program and these results are in agreement with some previous studies as well.…”
Section: Discussionsupporting
confidence: 93%
“…While lack of motivation and understanding do not explain low work capacities achieved among individuals with DS when appropriate testing and familiarization protocols are followed (Fernhall et al, 2013), physical activity levels do not further explain this phenomenon either with activity being similar to the general population (Mendonca, Pereira, & Fernhall, 2010). With mortality in ID commonly associated with a low intelligence quotient and poor self-care skills, it is important to point out that low aerobic capacity has also been strongly linked to morbidity and mortality among individuals with ID (Fernhall et al, 2001;Hayden, 1998).…”
mentioning
confidence: 94%
“…Still on the cardiorespiratory adaptations to training, the findings of this study showed a significant increase in pulmonary ventilation (VE) for young people who participated in the training program, whether aerobic or resistance. The increased maximum pulmonary ventilation in this population is interesting because due to the restricted size of airways, the small nasal passage and large tongue can obstruct breathing during exercise 11 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of intervention, the authors 14 found a reduction in heart rate in all stages of submaximal exercise. Other studies 11,21 , involving adults with DS found improvements in motion economy, expressed by reduction of oxygen uptake during submaximal exercise.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation